Problematika Frasa Tanpa Persetujuan Korban Dalam Peraturan Menteri Pendidikan Kebudayaan Riset Dan Teknologi Nomor 30 Tahun 2021 Tentang Pencegahan Dan Penanggulangan Kekerasan Seksual Di Perguruan Tinggi - Nur Anisah, Laili (Universitas Pancasakti Tegal, 2022)
The Ministry of Education and Culture in an effort to prevent and overcome sexual violence The Ministry of Education and Culture issued Regulation No. 30 of 2021 concerning the Prevention and Control of Sexual Violence in Higher Education. The Permendikbudristek is intended as a legal basis for the processing of cases of sexual violence that occur in the Higher Education environment. However, there were several problematic substances after the Permendikbudristek was ratified, one of which was the phrase